Development of Environmental Pollution Handling Flipbook Based on Surabaya Local Wisdom to Train Students’ Ethno-conservation - Dwi Wahyu Agustina; Fida Rachmadiarti; Sunu Kuntjoro (IJORER : International Journal of Recent Educational Research, 2023)
One of the efforts to deal with environmental pollution by exploring natural potentials and traditions in the local community is ethno-conservation education. This study aims to develop a flipbook of environmental pollution handling based on Surabaya's local wisdom to train students in Ethno-conservation. The type of research is Research and Development with the ADDIE model of Branch theory. Theoretical feasibility is reviewed from the results of expert validation, while empirical feasibility is examined from the readability test. The data obtained were analyzed by descriptive qualitative. The results obtained are a validation score of 3.88, a percentage of 97% and the category is excellent, and the legibility test is at level 10. Hence, the Flipbook has the potential to be used in learning the handling of environmental pollution based on Surabaya local wisdom to train students in ethno-conservation.